Pharmacists’ Knowledge and Perceptions of FDA Approval Standards and the Breakthrough Therapy Designation - Megan C. Herink; Kirbee Johnston; Kristin Breninger; Erin Wu; Adriane N. Irwin (Pharmacy, 2022)
The “breakthrough therapy” designation (BTD) is a recent mechanism implemented by the United States Food and Drug Administration (FDA) to expedite access to drugs that address unmet needs. The purpose of this study is to describe pharmacists’ knowledge of FDA drug-approval standards and knowledge and perceptions of the BTD. Pharmacists engaged in advanced clinical practice were identified through membership profiles of a professional pharmacy organization. Eligible participants were then sent a questionnaire to assess knowledge of FDA approval standards and the BTD. A total of 226 pharmacists responded. The majority of respondents were women (70.2%) and had completed post-graduate training (85.8%). Over half correctly answered at least two of three questions on FDA approval standards (58.1%) and the BTD (78.1%). Only 24.1% of respondents identified as being familiar with the BTD. The majority of pharmacists (62.8%) were certain that FDA-approved “breakthrough” drugs represented a major advance over currently approved therapies and most (88.5%) preferred the drug designated as “breakthrough” in a hypothetical scenario. In conclusion, pharmacists were able to correctly answer questions about FDA approval standards and the BTD. However, they were unfamiliar with the implications of a BTD and may overestimate the benefit demonstrated by these drugs. Future research should identify knowledge gaps in pharmacist understanding of regulatory mechanisms designed to expedite drug approval.